Microstructure evolution and mechanical properties degradation behavior of nuclear power pressure vessel steel induced by prolonged thermal aging - Tengfei Wang; Junkang Gao; Shaohong Li; Jun Li; Junwan Li; Hengyong Bu; Huarong Qi; Zhimin Li; Mengnie Li (Journal of Materials Research and Technology)
The microstructure evolution and mechanical properties of VVER 1000 RPV steel Cr–Ni–Mo–V after accelerated thermal aging at 480 °C for varying durations were thoroughly examined. It was revealed that the diminishing trend in tensile strength, impact energy and microhardness decreased as the aging period extended. The microstructure was meticulously characterized using optical microscopy, scanning electron microscopy, and transmission electron microscopy. It was found that with the prolongation of thermal aging time, the carbides were coarsened and transformed, and the large-sized carbides were redissolved into the matrix after a certain period of thermal aging. The increasing presence of M23C6 carbides over the duration of thermal aging indicated a transition from MC to M23C6, highlighting that the primary cause of property degradation during thermal aging was the coarsening of carbides.